2017
DOI: 10.1038/srep41121
|View full text |Cite
|
Sign up to set email alerts
|

A chemical genetic screen uncovers a small molecule enhancer of the N-acylethanolamine degrading enzyme, fatty acid amide hydrolase, in Arabidopsis

Abstract: N-Acylethanolamines (NAEs) are a group of fatty acid amides that play signaling roles in diverse physiological processes in eukaryotes. Fatty acid amide hydrolase (FAAH) degrades NAE into ethanolamine and free fatty acid to terminate its signaling function. In animals, chemical inhibitors of FAAH have been used for therapeutic treatment of pain and as tools to probe deeper into biochemical properties of FAAH. In a chemical genetic screen for small molecules that dampened the inhibitory effect of N-lauroylethan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Specifically, our data suggest that BC patients would benefit from an upregulation of FAAH expression and/or activity in the cancer cells, but due to the current technical limitations of gene therapy, a more rational approach to bring FAAH upregulation closer to the clinic would be to identify unequivocal upstream regulators that increase its expression or activity. Recently, the first compound ever reported to stimulate FAAH was isolated from Arabidopsis thaliana , thus providing a tool to downregulate the AEA tone in the cell 56 . Future studies may focus on the signaling pathways controlled by FAAH in the context of advanced BC, which could pave the way for the design of strategies and tools for the management of this malignant disease.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, our data suggest that BC patients would benefit from an upregulation of FAAH expression and/or activity in the cancer cells, but due to the current technical limitations of gene therapy, a more rational approach to bring FAAH upregulation closer to the clinic would be to identify unequivocal upstream regulators that increase its expression or activity. Recently, the first compound ever reported to stimulate FAAH was isolated from Arabidopsis thaliana , thus providing a tool to downregulate the AEA tone in the cell 56 . Future studies may focus on the signaling pathways controlled by FAAH in the context of advanced BC, which could pave the way for the design of strategies and tools for the management of this malignant disease.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the efficacy to rescue NAE12:0-induced phenotypes of root length, root hairs and cotyledon area, only one compound was identified-the 6-(2-methoxyphenyl)-1,3-dimethyl-5-phenyl-1Hpyrrolo [3,4-d]pyrimidine-2,4(3 H,6 H)-dione, named MDPD (Figure 3). Whereas the rescue was only partial for primary root length, it was complete both for root hairs and the cotyledon expansion phenotype [32]. In vitro amidohydrolase activity on the recombinant AtFAAH and FAAH from rat (ratFAAH) clearly revealed that MDPD is able to increase the enzymatic efficiency of AtFAAH (3-to-4 fold) but not of ratFAAH, suggesting that MDPD is specifically active on plant FAAH.…”
Section: Small Molecules To Gain Insights Into Plant Morphogenesis An...mentioning
confidence: 98%
“…In vitro amidohydrolase activity on the recombinant AtFAAH and FAAH from rat (ratFAAH) clearly revealed that MDPD is able to increase the enzymatic efficiency of AtFAAH (3-to-4 fold) but not of ratFAAH, suggesting that MDPD is specifically active on plant FAAH. [32]. Nevertheless, since MDPD can partially rescue the hypersensitive phenotype NAE12:0 of the Atfaah mutant seedlings, it seems likely that, in the absence of AtFAAH, it may function also by enhancing the activity of other amidohydrolases.…”
Section: Small Molecules To Gain Insights Into Plant Morphogenesis An...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the software used (String), each interaction score expresses an approximate confidence on a scale of 0 to 1 that the association is true, given all available evidence (Szklarczyk et al, 2019). Accordingly, the strongest neighbourhood interaction in our dataset was between the proteins FATTY ACID AMIDE HYDROLASE (FAAH), required in defence, and PYRIMIDINE 2 (PYD2), involved in nitrogen recycling from nucleobases, which is explained by the proximity in the genome of both genes (Zrenner et al, 2009;Khan et al, 2017). In the case of gene fusion channel, the interaction was strongest between CELL DIVISION CYCLE 5 (CDC5), essential for plant innate immunity, and MATERNAL EFFECT EMBRYO ARREST 29 (MEE29), needed in embryogenesis, because at least in the fungus Pneumocystis jirovecii orthologous proteincoding genes are fused into an only gene (Barcaccia and Albertini, 2013).…”
Section: Protein-protein Interactionsmentioning
confidence: 99%